Teaching Arabic for professional purpose: develop a pilot course for humanitarian volunteers in Malaysia - Ali, Asem Shehadeh Saleh (Universit Islam Riau, 2019)
Volunteers are less commonplace among Malaysians today. Prime Minister of Malaysia, Dato 'Sri Najib Abdul Razzaq, has encouraged volunteerism as a multiethnic Malaysian social lifestyle to make Malaysia a center and volunteer model. Showing statistics released by UNHCR in Malaysia in October 2019 that there are about 8645 registered refugees in Malaysia coming from Arab countries including Yemen, Syria, Iraq and Palestine. The refugees increasing every day, and this situation paves the way for Malaysians to participate in voluntary work. This study aims to achieve the following objectives: Statement of language requirements in the field of humanitarian work, to demonstrate skills to focus on humanitarian volunteers, and to design the standard statement of Arabic language for professional purposes in the field of humanitarian work.